Principal Leadership Performance Against Teachers in SMA 1 Manado - Meike D. Mamentu (Journal of International Conference Proceedings (JICP), 2018)
This study aims to determine how much influence principal leadership style on the performance of teachers at SMAN 1 Manado . Where is the leadership style of a principal is critical because it can affect the performance of teachers as well as to contribute to the achievement of the goals of the school .The method used in this study is a quantitative method , yaitru method of linking variables in the study of principal leadership style as the independent variable ( X ) and teacher performance as the dependent variable ( Y ) . From the results of the data analysis obtained by using simple regression y = 1.86 + 0.91 x it indicates that there is a positive relationship of leadership style of the Principal Teacher Performance wherein if the styles of leadership do principals of 1.86 would affect on teacher performance of 0.91. The influence of leadership style on teacher performance obtained r = 0.71 suggesting a positive relationship between the two variables . Thus the principal's leadership style affects the performance of existing teachers in SMA 1 Manado . By using the t test , t obtained 6.25 and 2.02 t obtained this table shows that the influence or relationship between variables X and Y is significant or meaningful ( significant ) because t 6.25 > 2.02 t table with thus leadership style has a positive effect on the performance of teachers at SMAN 1 Manado . Keywords: Leadership Style, Teacher Performance